PELATIHAN KLINIS SIRKUMSISI BAGI TENAGA KESEHATAN DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG 2025 - Mhd Nurhuda; Yusti Siana; Dian Puspita; Melya Susanti; Sri Nani Jelmila; Yuliza Birman; Nilas Warlem (Yayasan Nusantara Hasana Berdikari, 2025)
Circumcision is a medical procedure involving partial or complete removal of the foreskin (prepuce). This procedure is considered a minor surgical procedure. This activity aims to provide training to medical personnel at Siti Rahmah Islamic Hospital (RSI) Padang on circumcision techniques. Circumcision is often encountered in the community due to complications such as bleeding and delayed wound healing. Therefore, training is needed to acquire the latest knowledge, skills, and techniques for preventing complications. Conducting direct training with paramedics at Siti Rahmah Islamic Hospital (RSI) Padang on July 3, 2025. Direct intervention in the form of circumcision was provided to each participant (patient). The results of this circumcision training have trained and skilled paramedics at Siti Rahmah Islamic Hospital (RSI) to perform circumcision with minimal complications.